Stalk yield of sugarcane cultivars under different water regimes by subsurface drip irrigation - Aderson S. de Andrade Junior; Edson A. Bastos; Valdenir Q. Ribeiro; Candido Athayde Sobrinho; Paulo H. S. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the stalk yield of ten sugarcane cultivars (RB962962, RB931011, RB931530, RB98710, RB92579, RB867515, RB863129, SP791011, RB72545 and VAT90212) subjected to water deficit, full irrigation and water surplus by subsurface drip irrigation, during three cropping seasons (2011-2014). The experiment was conducted at the Experimental Field of Embrapa Meio-Norte, Teresina, Piauí State, Brazil, in dystrophic Red Yellow Argisol. The cultivars RB962962 (162.3 Mg ha-1) and RB867515 (158.5 Mg ha-1) have better stalk yield compared with other cultivars in all water regimes and cropping seasons.